Kompetencje społeczne nauczycieli – diagnoza i pomocowe implikacje - Piorunek , Magdalena; Werner, Iwona (Studia Edukacyjne, 2020)
The paper focuses on the diagnosis of the social competencies of the lower secondary school teachers and among students preparing for the teaching profession. The study used the Social Competencies Profile (PROKOS), which measures social competencies in five specific areas: assertiveness, cooperation, social mindedness, resourcefulness, and community awareness. Surprisingly, students exhibit higher levels of assertiveness and cooperation competencies than teachers. In the group of teachers, statistically significant differences were found between men and women at the level of all the competencies diagnosed. Professional advancement and teacher training did not produce different results. This shows that the level of social competence of teachers is unsatisfactory, especially as regards their ability to support young people.